Walking London's Circle Line: A Pedestrian Guide to Central London - Schwarzbach, Fredric (Hamilton Books, 2023)
Walking London’s Circle Line a pedestrian guide to the history, architecture, and curiosities of central London. It is comprised of a series of fifteen guided walks that begin and end at selected stations on the London Underground Circle Line. Opened in 1884, the Circle Line not only serves central London but helps define it. Each walk takes about two hours and collectively they range across the whole of central London, delving into its history from Roman times to the present day. It features many of London’s iconic attractions but also out of the way corners that hide in plain sight. Tourists and visitors will find it an invaluable guide to the richness of metropolitan life, while lifelong Londoners will be surprised at how much there is still to learn about their city.